SWEEPING WITH ALL GRAPHICAL INGREDIENTS IN A TOPOLOGICAL PICTUREBOOK - AKMAN, V; ARSLAN, A (Pergamon-Elsevier Science Ltd, 1992)
Sweeping is a powerful method to generate 3-D shapes in geometric modeling. In this paper we formulate a general matrix to give a mathematical definition of twisted-profiled sweep objects as a discrete approximation. While conceptually simple, our result is, to our best knowledge, the first precise formulation of sweeping with all graphical ingredients, viz. twisting, scaling, rotation, and translation. Twisted-profiled sweeping surfaces defined by contour, profile, trajectory, and guide curves are thus represented in concatenated matrix formulation. In addition, we give interactive methods to generate sweep objects and present sample figures produced within the framework of our implementation Tb, a topological picturebook.